Mathematical Model for the Prediction of Gas-Liquid Mass Transfer in Airlift Contactors - P Pasavant; P Wongsuchoto; V Suksoir (ASEAN Journal of Chemical Engineering, 2005)
A mathematical model was proposed to explain the gas-liquid mass transfer behavior in an airlift contactor (ALC). The model separated the airlift contactor into three sections: riser, gas separator, and downcomer. The riser and downcomer were described using the dispersion model whilst the gas separator was modeled as a .completely mixed tank. All parameters needed for the model were obtained from independent experiments both carried out in this work and reported elsewhere. Simulation results were compared with a number of experimental data obtained from the systems with various geometrical and operational conditions. It was shown that the model could predict the oxygen mass transfer between phases in the ALC with reasonable accuracy. Keywords: Airlift contactor (ALC), dispersion model, mass transfer, mathematical model, and verification.